Comparison of Safety Of Oral Ivermectin with Topical Permethrin in the Treatment of Scabies: A Comparative Study - Rishab Dev Tripathee; Seema Sitaula; Sanjeev Kharel (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: The mite Sarcoptes scabiei var. hominis is the cause of scabies, a skin illness. The Food and Drug Administration (FDA) approves permethrin cream (5%) for the treatment of scabies and is also recommended by the Centers for Disease Control and Prevention (CDC) as first-line topical therapy for scabies. Oral ivermectin, a novel antiparasitic agent that has been extensively used for several parasitic infections and can be used as an alternative approach for the treatment of scabies. This comparative study aimed to describe the adverse effects of ivermectin and permethrin and their comparison.